2006
DOI: 10.1007/s10649-006-8753-x
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction and Consolidation

Abstract: The framework for this paper is a recently developed theory of abstraction in context. The paper reports on data collected from one student working on tasks concerned with absolute value functions. It examines the relationship between mathematical constructions and abstractions. It argues that an abstraction is a consolidated construction that can be used to create new constructions. Newly formed constructions are fragile entities. In the course of consolidating a construction this student creates connections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 10 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…Most of the researchers carried out researches on abstraction in context "Recognizing", "Building-with" and "Constructing" as epistemic actions, (Altun & Kayapınar, 2011;Kidron & Dreyfus, 2010), while several researchers emphasized the consolidation process (Dreyfus & Tsamir, 2004;Tabach, Hershkowitz & Schwarz, 2006;Monaghan & Ozmantar, 2006;Dreyfus, Hadas, Hershkowitz & Schwarz, 2006) and characteristics of consolidation (Dreyfus & Tsamir, 2004, Tsamir & Dreyfus, 2005Anabousy & Tabach, 2015). Dreyfus and Tsamir (2004) carried out a study which revealed the characteristics of consolidation that emerges from a sequence of interviews about the comparison of infinite sets with a talented student.…”
Section: Abstraction In Context (Rbc+c Model)mentioning
confidence: 99%
“…Most of the researchers carried out researches on abstraction in context "Recognizing", "Building-with" and "Constructing" as epistemic actions, (Altun & Kayapınar, 2011;Kidron & Dreyfus, 2010), while several researchers emphasized the consolidation process (Dreyfus & Tsamir, 2004;Tabach, Hershkowitz & Schwarz, 2006;Monaghan & Ozmantar, 2006;Dreyfus, Hadas, Hershkowitz & Schwarz, 2006) and characteristics of consolidation (Dreyfus & Tsamir, 2004, Tsamir & Dreyfus, 2005Anabousy & Tabach, 2015). Dreyfus and Tsamir (2004) carried out a study which revealed the characteristics of consolidation that emerges from a sequence of interviews about the comparison of infinite sets with a talented student.…”
Section: Abstraction In Context (Rbc+c Model)mentioning
confidence: 99%
“…However, studies conducted especially over the last fifteen years have shown that consolidation of newly constructed mathematical knowledge plays an essential role in future learning (e.g., Tabach et al, 2006, Monaghan & Ozmantar, 2006. These studies suggest the importance of consolidation through activities focusing on the use of newly constructed mathematical structures in different contexts and with different dimensions.…”
Section: Repetition and Consolidationmentioning
confidence: 99%
“…This cognitive process repeated in different situations leads to the possibility of consolidating mathematical conceptions. Therefore, the iteration of these phases may help in the consolidation of such mathematical structures (MONAGHAN;OZMANTAR, 2006). From this perspective, the consolidation process of mathematical conceptions is another manifestation of reflective abstraction that leads to a new cognitive state.…”
Section: Two Manifestations Of Reflective Abstractionmentioning
confidence: 99%
“…Consequently, in order to give learners the opportunity to change their attention-focus and begin to see a set of activityeffect registers as a unified object (the identification of the regularity and/or the general aspect) (DÖRFLER, 2002) it will be necessary to create opportunities for the development of language-items for the new construction. This characteristic of the task has also been considered relevant in designing tasks to Different Moments in the Participatory Stage of the Secondary Students' Abstraction of... ROIG, A. I.; LLINARES, S.; PENALVA, M. C. consolidate a new construction (GARCÍA; LLINARES; SÁNCHEZ-MATAMOROS, 2010;MONAGHAN;OZMANTAR, 2006). In any event, more research is required to provide information that will be useful in reaching a clearer theoretical understanding of task-design, with all the obvious implications for the improvement of teaching methods.…”
Section: Two Manifestations Of Reflective Abstractionmentioning
confidence: 99%